2013
DOI: 10.1021/es402013t
|View full text |Cite
|
Sign up to set email alerts
|

Water Footprint Assessment for Wastewater Treatment: Method, Indicator, and Application

Abstract: The water footprint in terms of the sum of both direct and indirect water cost of wastewater treatment is for the first time accounted in this work. On the basis of the hybrid method as a combination of process analysis and input-output analysis, a detailed water footprint accounting procedure is provided to cover the supply chain of a wastewater treatment plant. A set of indices intending to reveal the efficiency as well as renewability of wastewater treatment systems are devised as parallels of corresponding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(33 citation statements)
references
References 30 publications
0
31
0
2
Order By: Relevance
“…The ecological footprint is a powerful indicator of the sustainability of development, as it considers the dynamics that are associated with the pressure that is exerted on the environment by the use of (renewable and non-renewable) resources as inputs and various outputs (such as waste or CO 2 ) [15]. The ecological footprint was modified to deal with assessing several applications such as the exergy based ecological footprint [16][17][18], water footprint [19], pig-biogas-fish system [20], fruit production systems [21], etc. Therefore, the ecological footprint can be utilized to measure the dependency of both consumers and producers on the global ecosystem [22].…”
Section: Ecological Footprintmentioning
confidence: 99%
“…The ecological footprint is a powerful indicator of the sustainability of development, as it considers the dynamics that are associated with the pressure that is exerted on the environment by the use of (renewable and non-renewable) resources as inputs and various outputs (such as waste or CO 2 ) [15]. The ecological footprint was modified to deal with assessing several applications such as the exergy based ecological footprint [16][17][18], water footprint [19], pig-biogas-fish system [20], fruit production systems [21], etc. Therefore, the ecological footprint can be utilized to measure the dependency of both consumers and producers on the global ecosystem [22].…”
Section: Ecological Footprintmentioning
confidence: 99%
“…All these analyses showed that virtual water accounting can bring comprehensive and accurate insights into water management issues. Recently, virtual water was also used to investigate the water issues within the specific engineering and technological systems or sectors, such as wastewater treatment system [26], building's engineering system [27] and service sector [28].…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, the application of the WF assessment methodology to WWTPs 95 is limited to the work of Liu et al, (2012) and Shao and Chen (2013). The first study only 96 estimated the grey water footprint of anthropogenic emissions to major rivers, not specifically 97 from WWTPs, and the second study only accounted for the blue water footprint (the study 98 also did not account for sludge treatment, which is extremely important in LCA).…”
mentioning
confidence: 99%